2020
DOI: 10.3390/s20154150
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based and Surface-Enhanced Raman Spectroscopy for Monitoring the Physio-Chemical Response of Thermophilic Bacterial Spores to Low Temperatures Exposure

Abstract: Monitoring the spore life cycle is one of the main issues in several fields including environmental control, sustainable ecosystems, food security, and healthcare systems. In this framework, the study of the living organism resistance to extreme conditions like those mimicking space environments is particularly interesting. The assessment of the local change of the pH level can be extremely useful for this purpose. An optical physiometer method based on the Raman response of the graphene, which is able to loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Therefore, it is feasible to indirectly detect Bacillus anthracis by quantification of the DPA content. Several chemical and biological techniques have been applied for the real-time and exact identification of trance DPA, 4 such as surface enhanced Raman spectroscopy (SERS), 5 polymerase chain reaction (PCR), 6 direct apparent fluorescence filtration (DEFT), 7 aerobic plate counting (APC), UV spectrophotometry and other methods. However, most of these methods suffer from complicated preprocessing and tedious operations, are time-consuming and require expensive instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is feasible to indirectly detect Bacillus anthracis by quantification of the DPA content. Several chemical and biological techniques have been applied for the real-time and exact identification of trance DPA, 4 such as surface enhanced Raman spectroscopy (SERS), 5 polymerase chain reaction (PCR), 6 direct apparent fluorescence filtration (DEFT), 7 aerobic plate counting (APC), UV spectrophotometry and other methods. However, most of these methods suffer from complicated preprocessing and tedious operations, are time-consuming and require expensive instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments were carried out either in space or in laboratories, by simulating the extreme environmental parameters that are typical of space and exoplanets, such as irradiation with UV and γ-rays, desiccation, low temperature values, etc. ( Di Donato et al, 2018b ; Romano et al, 2018 , 2022 ; Camerlingo et al, 2020 ). P. thermantarcticus viable cells and its spores were found to survive in a space simulated environment, which in turn lead to a new scenario called as the Panspermia theory that states that life on Earth could have originated from bacterial species from other places transported by solar pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SERS spectrometer is stable with low maintenance costs, and the operation is simple. 12,13 In this study, we tested the zeta potential of Candida and found that the surfaces of C. albicans, C. tropicalis, and C. krusei were all negatively charged. Thus, we selected AgNPs + as the SERS-enhanced substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SERS spectrometer is stable with low maintenance costs, and the operation is simple. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%